Is climate change causing increased rockfall frequency in Austria? - O. Sass; M. Oberlechner (Natural Hazards and Earth System Sciences, 2012)
Potentially, increasing rockfall hazards triggered by climate change are a major concern expressed both in scientific and non-scientific media. An existing rockfall inventory for Austria including 252 events from ca. 1900 to 2010, mainly from non-permafrost areas, was analysed. The correlation of events with temperatures is very weak and no increase of rockfall frequency during warmer periods was observed. The peak of rockfall activity is in spring, whereas in recent decades a secondary summer maximum appeared in the records. A possible reason for this shift is reduced rockfall activity in spring due to warmer winters. We conclude that a premature warning of increasing rockfall hazard, especially below the permafrost limit, is not supported by the existing data.